CONCEPT OF SEED DETERIORATION: REASON, FACTORS, CHANGES DURING DETERIORATION AND PREVENTIVE MEASURES TO OVERCOME SEED DEGRADATION (American International Journal of Agricultural Studies, 2023)
Seed deterioration is when a seed loses its vigor and eventually loses viability. Seed viability is an important trait that directly influences seedling emergence and crop yield. The rate of seed deterioration varies on several factors. Our main aims were to express the methods for testing seed deterioration, factors influencing seed aging, stages of seed deterioration, changes associated with seed deterioration, Practical approaches to overcome seed deterioration, and the role of reactive oxygen species during seed aging. From this investigation, it can be concluded that high temperatures and high relative humidity can hasten the degradation of seeds. An increase in the loss of seed leachate, a drop in respiration rates and ATP production, a loss of enzyme activity, and organelle structural breakdown are often seen as changes as seeds age. Various factors can cause seed aging, but the main cause is probably oxidative damage brought on by free radicals and reactive oxygen species (ROS). Protein oxidation, lipid peroxidation, chromosomal abnormalities, and DNA damage can all be induced by ROS, which can have critical interactions with any macromolecule of biological significance. In the early stages of imbibition, some repairs may occur, and seeds will lose their viability within a short period. Seed deterioration can be retrieved through different priming and exogenous application of plant growth regulators.JEL Classification Codes: Q1, Q2, N5.